GC - MS AND FTIR ANALYSIS OF BIOACTIVE COMPOUNDS PRESENT IN DIFFERENT EXTRACTS OF ERANTHEMUM PULCHELLUM -ANDREWS - DARMWAL, JYOTI; DHUNI, MANOJ; JOSHI, PUSHPA; RAWAT, NEELAM; KOSHYARI , VANDANA; KATHURIA, SHUBHAM (The Bioscan, 2023)
Eranthemum pulchellum, a tropical evergreen shrub from the Acanthaceae family, is widely distributed in various parts of India, China and Nepal. Previously, various parts of this plant were reported for the treatment of various ailments but no GC-MS analysis of this plant has been reported. Thus, the aim of the present study was to identify the important functional groups and phytochemical contents in methanol, ethyl acetate, and n-hexane extracts of E. pulchellum using a Fourier transform infrared spectrometer (FTIR) and gas chromatography-mass spectrometry (GC-MS). Gas chromatography-mass spectrometry results revealed 48 phytocompounds in methanol extract, 42 phytocompounds in ethyl acetate and 47 phytocompounds in n-hexane extracts. The major bioactive components are i-Propyl alpha-linolenate (16.45%) and Squalene (12.34%) in methanol extract, Eicosyl trifluoroacetate (20.44%) and Squalene in ethyl acetate, Eicosyl trifluoroacetate (20.59%) and Squalene (12.86%) in n-hexane extract. The FTIR spectra revealed the presence of functional groups such as alcohols, carboxylic acids, aromatics, alkanes, alkenes, alkyl halides and amines which indicates the presence of various metabolites in the extracts. It is concluded that the significant bioactive compounds are present in plant extracts and these constituents are responsible for the therapeutic effects of the plant.